A Li-rich Layered@Spinel@Carbon heterostructured cathode material for high capacity and high rate lithium-ion batteries fabricated via an in situ synchronous carbonization-reduction method1. Issue 7 (21st February 2015) - Xia, Qingbing; Zhao, Xinfu; Xu, Mingquan; Ding, Zhengping; Liu, Jiatu; Chen, Libao; Ivey, Douglas G.; Wei, Weifeng
<x xml:space="preserve">Abstract</x> A Li-rich Layered@Spinel@Carbon heterostructured cathode material for LIBs, which comprises Li-rich layered core, a spinel interlayer and a carbon nano-coating.